Being AND becoming a wise leader - Kessler, Eric H. (Journal of management, spirituality & religion, 2025)
Despite the burgeoning literature around leadership there is a lack of theoretical integration as well as practical inconsistencies in terms of how its insights relate to actually a) being a leader and b) becoming a leader. Utilizing a wisdom-based template offers a path to synergistically combine academic models so to gain a holistic understanding of its higher-order mega-competencies - foundational, multidimensional and context specific leadership tools - and its subsequent meta-heuristics - capacities for matching appropriate leadership identities, roles, and behaviors to address dominant leadership challenges. As such, and specifically by focusing on ideas seeded from the foundational work of Plato's Republic, this type of perspective represents a potentially useful approach for reconciling seemingly divergent approaches and advance how we might think about the leadership role and its intersection with transcendent ideas of reason, emotion, value, spirit, connection, and success.